2018
DOI: 10.1186/s12887-018-1027-9
|View full text |Cite
|
Sign up to set email alerts
|

Case report of severe myocarditis in an immunocompromised child with Respiratory Syncytial Virus infection

Abstract: BackgroundRespiratory syncytial virus (RSV) infection is common and may be severe among patients with preexisting cardiac anomalies, but direct involvement of myocardial damage is not common in those patients. Additionally, myocardial involvement has been rarely described among immune compromised children.Case presentationA 4-year-old girl with acute lymphoblastic leukemia who received maintenance chemotherapy in an outpatient clinic developed systemic inflammatory response syndrome. RSV infection was confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…RSV myocarditis is a well-known extrapulmonary manifestation of severe RSV infection [18]. Although RSV has been detected in human myocardial tissue on PCR [19], the occurrence of cardiogenic shock resulting primarily from heart failure has rarely been documented [20, 21]. Myocardial dysfunction seems a more common clinical picture, notably in infants or in children with congenital heart disease [2225].…”
Section: Discussionmentioning
confidence: 99%
“…RSV myocarditis is a well-known extrapulmonary manifestation of severe RSV infection [18]. Although RSV has been detected in human myocardial tissue on PCR [19], the occurrence of cardiogenic shock resulting primarily from heart failure has rarely been documented [20, 21]. Myocardial dysfunction seems a more common clinical picture, notably in infants or in children with congenital heart disease [2225].…”
Section: Discussionmentioning
confidence: 99%
“…A Rapid literature review showed three case reports [10][11][12] in addition to the cross-sectional study by Checchia et al 13…”
Section: Rsv Causing a Myocardial Inflammation Another Hypothesis?mentioning
confidence: 95%
“…A Rapid literature review showed three case reports 10–12 in addition to the cross‐sectional study by Checchia et al 13 which was used as a reference by Rossi et al (Summarized in Table 2). The age range of the retrieved cases (7 months to 7 years) exceeded the age range described in Rossi et al series.…”
Section: Manuscriptmentioning
confidence: 99%
“…1 There are few RSV-induced myocarditis case reports, especially in immunocompromised children. 2 This report aimed presenting an uncommon case of RSV cardiovascular manifestation in an immunocompetent adolescent outside of the usual risk group for complications. The study and consent waiver were approved by the local Review Board (CAAE: 54477821.9.0000.0071).…”
Section: Introductionmentioning
confidence: 99%